Security, privacy, and applied cryptography engineering : 8th International Conference, SPACE 2018, Kanpur, India, December 15-19, 2018, Proceedings /: 8th International Conference, SPACE 2018, Kanpur, India, December 15-19, 2018, Proceedings. (2018) - Unknown
No abstract available